DAMPAK STRUKTUR MODAL DAN PERTUMBUHAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN PADA PT ELECTRONIC CITY TBK PERIODE 2013-2022 - Gregorius Manetoferi Dea Resta; Supatmin Supatmin (LAP4B, 2025)
This study aims to determine the effect of Capital Structure proxied by Debt to Equity Ratio (DER) and Company Growth proxied by Return on Equity partially and simultaneously on Company Value proxied by Price Book Value (PBV) at PT Electronic City Tbk for the 2013-2022 period. The research method used is a quantitative research method. The data used is secondary data in the form of financial reports of PT Electronic City Tbk for the 2013-2022 period. The analysis methods used are descriptive analysis, classical assumption test, correlation coefficient, determination coefficient, simple linear regression analysis, multiple linear regression analysis and hypothesis testing with t-test and F-test using SPSS version 26. The partial results of the study showed that Debt to Equity Ratio (DER) has a t-count value <t-table (-0.741 <2.306), with a significant probability of 0.480> 0.05, so that partially Debt to Equity Ratio (DER) has no effect on Price Book Value (PBV), Return on Equity has a t-count value> t-table (4.038> 2.306) with a significant probability of 0.004 <0.05, so that partially ROE has an effect on PBV. The results of the simultaneous study between DER and ROE on PBV showed a F-count value> F-table (5.269> 4.74) with a significant value of 0.002b <0.05. So simultaneously DER and ROE have an effect on PBV